Energy Resource Scheduling in an Agriculture System Using a Decision Tree Approach - Abrishambaf, Omid (2022)
The present work was done and funded in the scope of project: Eco Rural IoT (TETRAMAX-VALUECHAIN-TTX-1), CEECIND/02887/2017, and UID/EEA/00760/2019 funded by FEDER Funds through COMPETE and by National Funds through FCT.